Temporary distribution of acute diarrheal diseases, its relationship with temperature and residual chlorine in drinking water in the city of Puno, Peru - Ferro Mayhua, Felix Pompeyo (2019)
The consumption of drinking water is vital for the daily living of human beings, and consequently an inadequate quality of it leads to the transmission of diseases. In this sense, the objective of the present investigation was to analyze the temporal distribution of Acute Diarrheal Diseases (ADDs) and their relationship with the temperature and residual chlorine of drinking water, in the city of Puno, Peru. The research is descriptive and explanatory, with a non-experimental and longitudinal research design type. It was used the data obtained from the Health Network from the Puno’s health region and the Municipal Sanitation Company, EMSA Puno. It was possible to identify that the residual chlorine in the water distribution system is above 0.5 mg/l. The cross correlation made shows that the historical variations of the ADDs are associated with temperature. Therefore, the ADDs are not directly caused by the water distributed by the company supplying drinking water, and there must be other factors in its endemic casuistry